J/[psi] and [psi]' total cross sections and formation times from data for charmonium suppression in pA collisions - He, Yong-Bin; Hüfner, Jörg; Kopeliovich, Boris Z. (Arxiv, 2000)
The recent data for E866 experiment on the x_F dependence for charmonium suppression in pA collisions at 800 GeV are analyzed using a time- and energy-dependent preformed charmonium absorption cross section σ_{abs}^ψ(τ,\sqrt{s}). For \sqrt{s}=10 GeV the initially (τ=0) produced premeson has an absorption cross section of σ_{pr}~3mb. At the same energy but for τ -> ∞ one deduces for the total cross sections σ_{tot}^{J/Psi N}=(2.8± 0.3)mb, σ_{tot}^{J/Psi N}= (10.5± 3.6)mb. The date are compatible with a formation time τ_{1/2}=0.6 fm/c.